PERAN DATA EXECUTIVE DAN CREATIVE COPYWRITER DALAM KAMPANYE KOMUNIKASI PEMASARAN DEBIURYN COSMETICS SEBAGAI PENGUATAN BRAND POSITIONING PADA KALANGAN REMAJA USIA 12–19 TAHUN DI KOTA SEMARANG - Nyndita Cahya Khumaira Nyndita Cahya Khumaira; Hapsari Dwiningtyas Sulistyani (Interaksi Online, 2026)
This fieldwork study examines the implementation of the marketing communication campaign "Stay Bright, Stay Youth" conducted by DeBiuryn, a teenage skincare brand targeting consumers aged 12–19 years in Semarang. The campaign was designed to increase brand awareness while supporting product sales performance through an integrated communication strategy utilizing Instagram and TikTok, reinforced by offline activities through the DeBiuryn Class Out program and Glow On the Booth DeBiuryn. The author contributed to the campaign as a data executive and creative copywriter, with responsibilities including campaign data management and analysis, as well as the development of taglines and captions aligned with the brand's characteristics. Based on the evaluation results, the campaign demonstrated positive outcomes, reflected in a significant increase in brand awareness from 14.6% to 84.8%. Sales performance of the Youth Series products also exceeded the predetermined targets, with Youth The Better Cleanser reaching 112 pieces from a target of 90 pieces, and Youth Go Away Sun SPF 30+++ achieving 92 pieces from a target of 90 pieces. These findings indicate that an integrated communication strategy can contribute to improving brand awareness and sales performance. The campaign also presents the potential to be developed as a sustainable program to maintain consumer engagement and strengthen the brand's presence in the teenage skincare market.